2022
DOI: 10.1101/2022.06.13.495988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

N1-Methylpseudouridine and pseudouridine modifications modulate mRNA decoding during translation

Abstract: The ribosome relies on hydrogen bonding interactions between mRNA codons and incoming aminoacyl-tRNAs to ensure rapid and accurate protein production. The inclusion of chemically modified bases into mRNAs has the potential to alter the strength and pattern of hydrogen bonding between mRNAs and aminoacyl-tRNAs to alter protein synthesis. We investigated how the N1-methylpseudouridine (m1Ψ) modification, commonly incorporated into therapeutic and vaccine mRNA sequences, influences the ability of codons to react … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Particularly, N1-methylpseudouridine has been used in the development of mRNA vaccines against COVID-19 disease32 and there is an immensely growing interest for this modification in the field of mRNA therapeutics in the current years. Such mRNA vaccines containing m 1 Ψ have been reported to show high stability and efficacy over those containing the canonical counterpart 32,A recent study by Monroe et al71 revealed the alteration of mRNA decoding as a result of Ψ and m 1 Ψ modifications during translation process and their study also suggested the context-dependent modulation of codon:anticodon base pairing interactions by Ψ and m 1 Ψ. Our study suggests the ability of m 1 Ψ to form more stable base pairs with the canonical residues compared to U or Ψ.…”
mentioning
confidence: 99%
“…Particularly, N1-methylpseudouridine has been used in the development of mRNA vaccines against COVID-19 disease32 and there is an immensely growing interest for this modification in the field of mRNA therapeutics in the current years. Such mRNA vaccines containing m 1 Ψ have been reported to show high stability and efficacy over those containing the canonical counterpart 32,A recent study by Monroe et al71 revealed the alteration of mRNA decoding as a result of Ψ and m 1 Ψ modifications during translation process and their study also suggested the context-dependent modulation of codon:anticodon base pairing interactions by Ψ and m 1 Ψ. Our study suggests the ability of m 1 Ψ to form more stable base pairs with the canonical residues compared to U or Ψ.…”
mentioning
confidence: 99%
“…Consistent with this expectation, translation elongation rates on fully Ψ-modified transcripts in reconstituted bacterial translation systems were reduced 3-fold and thus greater than expected if the reduced GTPase activation had been the sole contributing factor. Moreover, increased amino acid misincorporation was observed specifically on Ψ-containing codons in bacterial and cultured human cells ( Eyler et al, 2019 ), Ψ incorporation into stop codons was observed to cause increased non-sense suppression ( Karijolich and Yu, 2011 ), and a recent study provided direct evidence for changes in near-cognate tRNA interactions on m1Ψ-modified codons ( Monroe et al, 2022 ). Together these results suggest that modification of transcripts with Ψ or m1Ψ alters competition from near-cognate tRNAs, thereby leading to general ribosome slow-down as well as reduced translational accuracy.…”
Section: Nucleotide Modifications and Translational Efficiencymentioning
confidence: 99%